The Application of Contextual Teaching and Learning for Increasing Learning Outcomes and Reducing Anxiety in Elementary School Mathematics - Farida Yunitasari; Mukti Sintawati; Al-Rashiff Hamjilani Mastul (International Journal of Learning Reformation in Elementary Education, 2023)
The study aimed to determine the effectiveness of Contextual Teaching and Learning (CTL) in reducing and improving learning outcomes and math anxiety among students at a private elementary school in Indonesia. The research utilized a one-group control pre-posttest design with a sample of 51 4th-grade  students. The study used a combination of pre-test and post-test and a closed-ended questionnaire as the data collection instruments. The independent variable in the study was CTL, while the dependent variables were learning outcomes and math anxiety. The paired t-test showed a significant increase in the students' average learning outcomes and a decrease in the average math anxiety levels. The findings suggest that implementing CTL is a practical approach to reducing math anxiety and improving student learning outcomes.